2004
DOI: 10.2527/2004.822526x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gender and slaughter weight on the growth performance, carcass traits, and meat quality characteristics of heavy pigs1

Abstract: Crossbred pigs (n = 192) from Piétrain x Large White sires mated to Landrace x Large White dams, with a mean BW of 75 +/- 1.3 kg, were used to investigate the effects of gender and slaughter weight (SW) on growth performance, carcass characteristics, and meat quality. Pens of pigs (eight pigs/pen) were assigned randomly to one of six treatments arranged in a 2 x 3 factorial design with two genders (barrows or gilts) and three SW (116, 124, or 133 kg). Each treatment was replicated four times. Over the entire t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
87
7
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 28 publications
45
87
7
7
Order By: Relevance
“…Shrink loss was not affected by castration, even though BF was thicker in CG than in IG. Similar data have been reported by Latorre et al (2004). Shoulder and trimmed primal cut yields were higher in IG than in CG, consistent with data of Serrano et al (2008 and2009a) who observed higher shoulder yield in IG from Iberian 3 Duroc pigs.…”
Section: Carcass Traitssupporting
confidence: 90%
See 1 more Smart Citation
“…Shrink loss was not affected by castration, even though BF was thicker in CG than in IG. Similar data have been reported by Latorre et al (2004). Shoulder and trimmed primal cut yields were higher in IG than in CG, consistent with data of Serrano et al (2008 and2009a) who observed higher shoulder yield in IG from Iberian 3 Duroc pigs.…”
Section: Carcass Traitssupporting
confidence: 90%
“…The IMF, crude protein and moisture content of the LT samples were determined with a near infrared transmittance meat analyzer (Infratec R 1265, Tecator, Hö ganä s, Sweden) as described by Latorre et al (2004). Drip loss was determined using 15-mm thick LT slices excised from each thawed chop.…”
Section: Husbandry and Dietsmentioning
confidence: 99%
“…Previous studies showed some or no effect of slaughter weight on meat quality traits (Latorre et al, 2004;Piao et al, 2004;Correa et al, 2006). However, the present study demonstrated the developmental changes of meat quality parameters of Jinhua pigs and Landrace, and breed differences.…”
Section: Discussioncontrasting
confidence: 68%
“…Although some studies have shown no influence of age on meat color even for wide ranges of slaughter weight (Weatherup et al, 1998;Serrano et al, 2008a), most studies agree on the beneficial effect of increased age on redder, darker and higher myoglobin content (Mayoral et al, 1999;Latorre et al, 2004). The trend followed by the data agree with such observations (a* or myoglobin content increasing as age increased).…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, restrictions of feed intake in the older pigs and higher feed allowance for the younger pigs during the pre-Montanera phase are necessary to afford that pigs with different ages achieve 160 kg BW at slaughter (Daza et al, 2006 and. Several previous studies have reported the effect of age on meat and fat quality of commercial (not autochthonous) pigs reared indoors (Leach et al, 1996;Weatherup et al, 1998;Latorre et al, 2004). However, this information in Iberian pigs is scarce and based on empirical observations.…”
Section: Introductionmentioning
confidence: 99%